Highly sensitive and selective detection of ethanol vapor using flame-spray-made CeOx-doped SnO2 nanoparticulate thick films - Kotchasak N. (2017)
© 2017 Elsevier B.V. In the present work, flame-spray-made CeO x -doped SnO 2 nanoparticles with 0.1–1 wt% Ce contents were systematically studied for ethanol detection. Structural characterizations by electron microscopy, Nitrogen adsorption and X-ray analysis indicated that SnO 2 nanoparticles were highly crystalline with tetragonal structure and CeO x crystallites with mixed Ce 3+ and Ce 4+ oxidation states should form a solid solution with SnO 2 matrix. The sensing films were tested towards 3–200 ppm ethanol at operating temperatures ranging from 200 to 400 °C in dry air. Gas-sensing results demonstrated that the SnO 2 sensing film with the optimal Ce content of 0.5 wt% exhibited a very high response of ∼2654–200 ppm ethanol with a short response time of 1.1 s at the optimal operating temperature of 350 °C. Moreover, the optimal sensor displayed high ethanol selectivity against C 3 H 6 O, CH 4 , H 2 , NO 2 , H 2 S and H 2 O. Therefore, the flame-made CeO x -doped SnO 2 sensor is a promising candidate as a sensitive and selective ethanol detector for drunk-driving and biomedical applications.